Modified Huangqi Chifeng Decoction Attenuates Proteinuria by Reducing Podocyte Injury in a Rat Model of Immunoglobulin a Nephropathy - Chang, Meiying; Yang, Bin; Li, Liusheng; Si, Yuan; Zhao, Mingming; Hao, Wei; Zhao, Jinning; Zhang, Yu (Frontiers in Pharmacology, 2021)
Modified Huangqi Chifeng decoction (MHCD) has been used to reduce proteinuria in immunoglobulin A nephropathy (IgAN) for many years. Previously, we have demonstrated its protective role in glomerular mesangial cells. Podocyte injury, another key factor associated with proteinuria in IgAN, has also attracted increasing attention. However, whether MHCD can reduce proteinuria by protecting podocytes remains unclear. The present study aimed to investigate the protective effects of MHCD against podocyte injury in a rat model of IgAN. To establish the IgAN model, rats were administered bovine serum albumin, carbon tetrachloride, and lipopolysaccharide. MHCD in three doses or telmisartan was administered once daily for 8 weeks (n = 10 rats/group). Rats with IgAN developed proteinuria at week 6, which worsened over time until drug intervention. After drug intervention, MHCD reduced proteinuria and had no effect on liver and kidney function. Furthermore, MHCD alleviated renal pathological lesions, hyperplasia of mesangial cells, mesangial matrix expansion, and podocyte foot process fusion. Western blot analysis revealed that MHCD increased the expression of the podocyte-associated proteins nephrin and podocalyxin. Additionally, we stained podocyte nuclei with an antibody for Wilms’ tumor protein one and found that MHCD increased the podocyte number in rats with IgAN. In conclusion, these results demonstrate that MHCD attenuates proteinuria by reducing podocyte injury.